Mesoscale Models for the Study of Emergent Behaviors Arising from Protein Interactions - Bueno Basurco, Carlos Andres (2022)
Proteins are versatile biopolymers in living systems that show a great diversity of functions based on the order of their amino acids. Many protein functions, whether mechanical or regulatory, emerge from interactions with other proteins and macromolecules. This dissertation describes the development and adaptation of new computational models to investigate structural and dynamic properties of protein interactions. Two main systems were investigated: the regulation of the actin cytoskeleton and the control of DNA transcription by nuclear factor B (NF-kB). During the study of the regulation of the actin cytoskeleton, mechanical and dynamic properties were estimated using polymer theory. A simplified model of actin filament polymerization was developed. Through simulations, it was shown that actin networks containing Arp2/3 undergo abrupt releases of tension. For the study of DNA interactions with proteins, a new procedure was implemented to simulate protein and DNA dynamics in mesoscopic systems, accelerating the simulation speed 30 times compared to previous methods. This model was used to understand the affinity of the NF-κB heterodimer for DNA compared to the NF-κB homodimer.